Extended Endonasal Endoscopic (EEE) Surgery with Almost No Use of Adjuvant Radiotherapy for Juvenile Nasopharyngeal Angiofibroma (JNA) - Shamsul Alam; Bipin Chaurasia; Mohsin Ali Farazi; Gianluca Ferini; Abu Saleh Mohammad Abu Obaida; Atiqul Islam; Abu Naim Wakil Uddin; Asifur Rahman (Medicina, 2023)
Background and Objectives: Juvenile nasopharyngeal angiofibroma (JNA) is an angiomatous hamartoma of the nasal cavity. It is a benign but locally aggressive vascular tumor of the nasopharynx affecting adolescent males. Many surgical procedures are in practice, but the extended endonasal endoscopic (EEE) approach for JNAs is a suitable and effective technique. Materials and Methods: Fifteen adolescent patients having JNA who underwent extended endonasal endoscopic (EEE) surgery from January 2010 to January 2022 were studied retrospectively. Patients having residual and recurrent JNAs and those who underwent surgery other than EEE were excluded. Results: The average age of the patients was 18.3 years of age. A total of six patients (40%) each had stage V and IV while three patients (20%) had stage III JNAs. Gross total removal was achieved in eight (53.3%) patients and seven (43.7%) had partial removal. There was no per or postoperative mortality. All the patients had at least 3 years of postoperative follow-up and during follow-ups, seven patients were found to have residual tumors, and two had recurrences. Discussion: During the last decades, the endoscopic approach for the resection of JNAs has gained increasing popularity due to its obvious advantages over transfacial approaches. The magnified and angled field of view “behind the corner” helping in a more complete inspection for the resection and shorter hospitalization time makes it a better choice than the other approaches. Conclusions: Endoscopy is an excellent approach for primary JNA. It allows well visualization and precise removal of the angiofibroma. An endoscopic multiangle, multicorridor skull base approach including Denker’s anteromedial maxillotomy is suitable and preferable for the resection of extensive JNAs.